The opportunities and value-adding activities of buy-back centres in South Africa's recycling industry: A value chain analysis. (May 2019) - Viljoen, Jacoba; Blaauw, Derick; Schenck, Catherina
This paper investigates the entrepreneurial opportunities and value-adding activities of buy-back centres in the recycling industry. Using Porter's firm-level value chain framework as theoretical framework for this analysis, a concurrent mixed method design was used to collect information from 67 buy-back centres across South Africa by means of face-to-face interviews, accompanied with a questionnaire with open-ended and close-ended questions. Buy-back centres' competitive advantage is that they have the facilities to add value to the recyclables according to the recycling industry's standards and specifications. To be viable, they need to attract large and sustainable volumes of recyclables, which often poses a challenge. Increased volumes of recyclables can translate into more jobs and income earning opportunities at all hierarchical levels in the recycling industry. A recycling model that increases the volumes of recyclables recovered by buy-back centres through informal sector activities is proposed. Such a model should facilitate changing citizen behaviour and implementation of, among others, responsible separation at source programmes to increase the volumes of cleaner recyclables. Increased supplies of recyclables should, however, be accompanied by an increase in the demand for products made from recyclables, to absorb the increased supply.